Determinants of outcomes in patients with pulmonary embolism and recent COVID-19 infection - S K Kononov; O. V. Solovev; A. R. Kraev; U. A. Ralnikova; E. V. Grebeneva (Российский кардиологический журнал, 2024)
Aim. To study the factors influencing outcomes in patients with pulmonary embolism (PE) and recent coronavirus disease 2019 (COVID-19).Material and methods. This retrospective observational study was conducted involving patients hospitalized in the emergency cardiology department from January 2020 to December 2021. Two groups of patients were analyzed depending on the presence of recent (up to 3 months) COVID-19.Results. A total of 113 patients hospitalized with PE met the inclusion criteria. Of these, 44 and 69 patients were with and without recent COVID-19, respectively. Mortality rate in the early period of the 2020-2021 pandemic was 23,5% and 7,5% in the group with and without recent COVID-19, respectively, p=0,023 (χ2=5,19). Patients with recent COVID-19 more often had peripheral pulmonary artery thrombosis, less often classic signs of PE. Patients with a fatal outcome more often had type 2 diabetes, higher blood troponin levels, estimated risk score values, lower mean platelet values, glomerular filtration rate, had worse hemodynamic parameters at the time of hospitalization, higher pulmonary artery pressure according to echocardiography. Among all the factors, the following had the greatest adverse effect: low systolic and diastolic blood pressure at the time of hospitalization, decreased glomerular filtration rate, high sPESI score risk.Conclusion. Even taking into account the pandemic end, it is important to study the factors influencing the PE course in COVID-19. This may be important when assessing long-term complications. Patients with PE and recent COVID-19 have distinctive clinical features and a tendency to higher mortality in the early pandemic period. Mortality is higher in the presence of both factors due to the severity of the previous infection and previously studied factors determining the unfavorable prognosis of PE.